Coexistence of pan-hypogammaglobulinaemia and primary ciliary dyskinesia. Issue 5 (24th May 2022) - S Kumar, Swasthi; Ray, Animesh; Kabra, Sushil Kumar; Sinha, Sanjeev
Abstract : A patient, an adolescent male, presented to us with complaints of recurrent respiratory tract infections since childhood. Differentials considered were cystic fibrosis (CF), bronchial asthma with allergic bronchopulmonary aspergillosis (ABPA), primary ciliary dyskinesia (PCD) and primary immunodeficiency disorders. Sweat chloride test, total IgE and Aspergillus fumigatus specific serum IgE and IgG levels were normal ruling out CF and ABPA. Nasal nitric oxide (NO) screening test showed reduced NO levels, and high-speed video microscopy of nasal scrapings showed stiff beating cilia with reduced ciliary beat frequency confirming the diagnosis of PCD. Immunodeficiency workup showed reduced serum IgG, IgA and IgM, when repeated on two separate occasions when the patient was not harbouring any active infection, suggestive of pan-hypogammaglobulinaemia. Thus, a diagnosis of coexistent PCD and pan-hypogammaglobulinaemia was made. Detection of immunodeficiency disorders is important in patients with PCD as they may benefit from immunoglobulin replacement.